1995
DOI: 10.1097/00000542-199510000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sufentanil on Cerebral Hemodynamics and Intracranial Pressure in Patients with Brain Injury

Abstract: The current data show that sufentanil (3 micrograms/kg intravenous) has no significant effect on middle cerebral artery blood flow velocity and ICP in patients with brain injury, intracranial hypertension, and controlled MAP. However, transient increases in ICP without changes in middle cerebral artery blood flow velocity may occur concomitant with decreases in MAP. This suggests that increases in ICP seen with sufentanil may be due to autoregulatory decreases in cerebral vascular resistance secondary to syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…However, increases in ICP along with infusion of opioids were always associated with decreases in MAP, suggesting that a rise in ICP was related to autoregulatory vasodilation and increased cerebral blood volume secondary to systemic hypotension. This is supported by an investigation in patients with brain injury and sufentanil infusion, where ICP periodically increased concomitant with a decrease in MAP of >10 mmHg but was unchanged in patients with MAP-control (7). In that study CBFV (as an index of flow) in the middle cerebral artery remained constant after sufentanil administration, which further supports the autoregulatory hypothesis (7).…”
Section: Discussionmentioning
confidence: 53%
“…However, increases in ICP along with infusion of opioids were always associated with decreases in MAP, suggesting that a rise in ICP was related to autoregulatory vasodilation and increased cerebral blood volume secondary to systemic hypotension. This is supported by an investigation in patients with brain injury and sufentanil infusion, where ICP periodically increased concomitant with a decrease in MAP of >10 mmHg but was unchanged in patients with MAP-control (7). In that study CBFV (as an index of flow) in the middle cerebral artery remained constant after sufentanil administration, which further supports the autoregulatory hypothesis (7).…”
Section: Discussionmentioning
confidence: 53%
“…As opposed to bolus, a continuous infusion of sufentanil did not alter MAP and ICP (1). Werner et al (19) emphasized the role of MAP, showing that a bolus of sufentanil did not change ICP when MAP was maintained constant by the use of a norepinephrine infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cerebrovascular effects of such drugs remain controversial. Studies in laboratory animals and humans have shown increases, decreases or no change in ICP after opioid administration (109)(110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120) . Most of these studies find a concomitant decrease in systemic arterial pressure and, recently, it has been suggested that reduced MAP could in fact be responsible for the increases in ICP observed after the administration of potent opioids such as sufentanil (107) .…”
Section: Opiodsmentioning
confidence: 99%